THE WEB BASED DESIGN OF POLTEKAD ELECTRONIC DETECTOR FOR COVID-19 - Perwira, Adrian Mitra; Widiatmoko, Dekki; Kholid, Fajar (Jurnal Elkasista, 2021)
The first-ever Covid-19 virus Pandemic was found in Wuhan, China in December 2019. This virus has become a pandemic and become the cause of death for many people. This Virus spreads rapidly and that's why it becomes every country's concern. The Covid-19 Virus can be detected by a method called PCR Swab Test. The Swab and PCR method can't be separated from defining a suspect result of Covid-19. Even more, Swab tests and PCR have become an important requirement for traveling. But the Test is so costly and takes a long time to get the result where it becomes a new problem. Hence, there is a device called Poltekad Electronic Detector that can detect a suspect of Covid-19 based on Body Temperature, Blood Pressure, Heartbeat, and Oxygen level on blood. All these parameters will be used by a smart system to draw a conclusion and showing it on a Web Server. This research using some of the methods used in sensor calibration thus makes the output of the device is corresponding to the Health Equipment Standard. According to the result of this research, the device could read a parameter and then draw a conclusion about the suspect and also send the data to the Web Server so the data can be accessed from a PC or a Smartphone. The result from the Web Server can be printed in PDF Format.